Quality Upgrading and Export Performance in the Asian Growth Miracle - Papageorgiou, Chris; Perez-Sebastian, Fidel; Spatafora, Nikola (Washington, D.C. : International Monetary Fund, 2019)
We explore the contribution of product-quality upgrading to the export performance of six fast-growing Asian economies: China, India, Indonesia, Malaysia, South Korea, and Thailand. We focus on measuring the impact of quality upgrading on the changes in these countries' sectoral export shares during 1970-2010. We build a multisector Ricardian trade model which allows for changes in product quality, and calibrate it to generate predictions about export volumes. Unlike previous literature, our approach allows estimation without employing domestic production data. Our results point to quality upgrading being a key driver of export shares.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet